A Compendium of the laws of the Church of Scotland - Steuart, Walter d.; Hill, George (Edinburgh Printing and Pub. Co., 1837)
Collections and observations concerning the worship, discipline, and government of the Church of Scotland in four books / Walter Steuart --Extracts from "Theological institutes" / George Hill -- An abridgement of the Acts of the General Assembly of the Church of Scotland from 1560 to 1830 inclusive.